2019
DOI: 10.1002/jcb.28356
|View full text |Cite
|
Sign up to set email alerts
|

Menadione‐induced apoptosis in U937 cells involves Bid cleavage and stefin B degradation

Abstract: Earlier studies showed that the oxidant menadione (MD) induces apoptosis in certain cells and also has anticancer effects. Most of these studies emphasized the role of the mitochondria in this process. However, the engagement of other organelles is less known. Particularly, the role of lysosomes and their proteolytic system, which participates in apoptotic cell death, is still unclear. The aim of this study was to investigate the role of lysosomal cathepsins on molecular signaling in MD-induced apoptosis in U9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Treatment with the ROS scavenger NAC almost completely restored cell viability (Fig. 5C), indicating that ROS production is the lethal mechanism induced by menadione in these experiments and not induction of apoptosis (Bozic, Bidovec, Vizovisek, Dolenc, & Stoka, 2019) or other mechanism. In contrast, inhibition of necroptosis by necrostatin-1s (RIPK1), GSK'872 (RIPK3) and necrosulfonamide (MLKL) did not prevent the cell death induced by menadione (Fig.…”
Section: Menadione-induced Ros Do Not Enhance Necroptosis By a Positive Feedback Loop In Macrophagesmentioning
confidence: 61%
“…Treatment with the ROS scavenger NAC almost completely restored cell viability (Fig. 5C), indicating that ROS production is the lethal mechanism induced by menadione in these experiments and not induction of apoptosis (Bozic, Bidovec, Vizovisek, Dolenc, & Stoka, 2019) or other mechanism. In contrast, inhibition of necroptosis by necrostatin-1s (RIPK1), GSK'872 (RIPK3) and necrosulfonamide (MLKL) did not prevent the cell death induced by menadione (Fig.…”
Section: Menadione-induced Ros Do Not Enhance Necroptosis By a Positive Feedback Loop In Macrophagesmentioning
confidence: 61%
“…Menadione (2-methyl-1,4-naphthoquinone; MD, vitamin K3) is a lipid-soluble synthetic analog of vitamin K, metabolized by the human body into menaquinone (vitamin K2). Numerous studies showed potent anticancer activity of MD in various cancer cell lines, with both antiproliferative and direct cytotoxic action resulting in caspase-dependent [ 3 6 ], caspase-independent apoptosis [ 7 ], necroptosis [ 8 ], or necrosis-like cell death [ 9 ]. The main mechanism of MD cytotoxic action is closely related to reactive oxygen species (ROS) produced during its metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…U937 cells have the peculiarity to express many of the monocytic-like characteristics and were selected as a model cell line since autophagy plays an important role in acute leukemias [13], and in addition, this pathway seems to play a pivotal role in the growth and differentiation of this cell line [14]. Furthermore, the U937 cell line shows sensitivity to the drugs selected for this study [1518].…”
Section: Introductionmentioning
confidence: 99%